2022
DOI: 10.3390/jpm12060957
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Machine Learning Procedures in Orthodontics: What Is Still Missing?

Abstract: Artificial intelligence (AI) models and procedures hold remarkable predictive efficiency in the medical domain through their ability to discover hidden, non-obvious clinical patterns in data. However, due to the sparsity, noise, and time-dependency of medical data, AI procedures are raising unprecedented issues related to the mismatch between doctors’ mentalreasoning and the statistical answers provided by algorithms. Electronic systems can reproduce or even amplify noise hidden in the data, especially when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Another study found that, compared to other radiographic techniques, cephalograms provide quantitative and qualitative results for anatomical landmark detection ( Bichu et al, 2021 , Joda and Pandis, 2021 , Liu et al, 2021 , Auconi et al, 2022 ). Skeletal landmark detection improves the accuracy of quantitative analyses as it identifies reference points.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that, compared to other radiographic techniques, cephalograms provide quantitative and qualitative results for anatomical landmark detection ( Bichu et al, 2021 , Joda and Pandis, 2021 , Liu et al, 2021 , Auconi et al, 2022 ). Skeletal landmark detection improves the accuracy of quantitative analyses as it identifies reference points.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning is a multidisciplinary technique that combines statistics and computer science and uses a variety of strategies and algorithms to arrive at the best model ( 11 ). Compared with traditional statistical methods that concentrate on the causality of hypothesis testing and the significance of model features, machine learning focuses more on the downscaling of high-dimensional data and the predictive performance and generalization of models ( 12 , 13 ). As a result, machine learning is better suited for analyzing complex and large quantities of data (e.g., gene expression analysis, image feature extraction, drug sensitivity prediction, etc.).…”
Section: Introductionmentioning
confidence: 99%